Mfn2 deficiency links age-related sarcopenia and impaired autophagy to activation of an adaptive mitophagy pathway - Sebastián, David; Sorianello, Eleonora; Segalés, Jessica; Irazoki, Andrea; Ruiz-Bonilla, Vanessa; Sala, David; Planet, Evarist; Berenguer-Llergo, Antoni; Muñoz, Juan Pablo; Sánchez-Feutrie, Manuela; Plana, Natàlia; Hernández-Álvarez, María Isabel; et al. (The EMBO journal, 2016)
Mitochondrial dysfunction and accumulation of damaged mitochondria are considered major contributors to aging. However, the molecular mechanisms responsible for these mitochondrial alterations remain unknown. Here, we demonstrate that mitofusin 2 (Mfn2) plays a key role in the control of muscle mitochondrial damage. We show that aging is characterized by a progressive reduction in Mfn2 in mouse skeletal muscle and that skeletal muscle Mfn2 ablation in mice generates a gene signature linked to aging. Furthermore, analysis of muscle Mfn2‐deficient mice revealed that aging‐induced Mfn2 decrease underlies the age‐related alterations in metabolic homeostasis and sarcopenia. Mfn2 deficiency reduced autophagy and impaired mitochondrial quality, which contributed to an exacerbated age‐related mitochondrial dysfunction. Interestingly, aging‐induced Mfn2 deficiency triggers a ROS‐dependent adaptive signaling pathway through induction of HIF1α transcription factor and BNIP3. This pathway compensates for the loss of mitochondrial autophagy and minimizes mitochondrial damage. Our findings reveal that Mfn2 repression in muscle during aging is a determinant for the inhibition of mitophagy and accumulation of damaged mitochondria and triggers the induction of a mitochondrial quality control pathway. Synopsis Reduced muscle mitochondrial fusion protein Mfn2 is a determinant for age‐induced decay of mitochondrial function and quality, contributing to age‐associated metabolic alterations and sarcopenia. Aging is characterized by a reduction of Mfn2 protein expression in skeletal muscle. Reduction in Mfn2 impairs mitochondrial quality control and mitochondrial function in skeletal muscle. Mfn2‐deficient mice show unhealthy aging characterized by impaired metabolic homeostasis and sarcopenia. Reduction in Mfn2 triggers a mitochondrial retrograde signalling pathway in order to minimize mitochondrial damage. Graphical Abstract Reduced muscle mitochondrial fusion protein Mfn2 is a determinant for age‐induced decay of mitochondrial function and quality, contributing to age‐associated metabolic alterations and sarcopenia.